No influence of sex on the relationship between schizotypy factors and executive control across the schizophrenia spectrum. (April 2022) - Gaillard, Alexandra; Tan, Eric J.; Carruthers, Sean P.; Gurvich, Caroline; Hughes, Matthew E.; Neill, Erica; Sumner, Philip J.; Van Rheenen, Tamsyn E.; Rossell, Susan L.
Abstract: Sex differences in symptoms and executive control across schizophrenia spectrum disorders (SSD) are consistently reported. Similarly, these findings of sex differences are also observed in schizotypy, that is, schizophrenia-like features occurring in healthy individuals in the absence of a clinical diagnosis. This study aimed to examine the relationships between performance on three major domains of executive control: performance monitoring, response inhibition, and cognitive set-shifting, and schizotypy factor scores in both SSD patients and healthy controls (HCs), and whether sex moderated any relationships observed. A total of 111 (67 males and 44 females) patients with SSD and 258 (129 males and 129 females) HCs were included in this study. Schizotypal personality traits (in both SSD and HC) was assessed using the Oxford-Liverpool Inventory of Feelings and Experiences (O-LIFE). Executive control performance was assessed using seven tasks. Stepwise linear regressions revealed that performance on cognitive set-shifting tasks was significantly associated with the introvertive anhedonia, cognitive disorganisation, and unusual experiences subscales of the O-LIFE. When sex was examined as a moderator, it was not a significant moderator of any of the relationships between cognitive set-shifting tasks and schizotypy factors. The results suggest that independent of sex, cognitive set-shifting ability is associated to an increased vulnerability to schizotypal personality traits, although performance monitoring and response inhibition did not.